THE BASES OF THE MANAGEMENT OF SOCIAL PROJECTS OF BUSINESS - O. B. Zilberstein; T. Y. Shahnes (Модернизация, инновация, развитие, 2016)
In article on wide material the author opens basic approaches to formation of the theoretical base of management of social projects of business.The purpose of work is generalization of theoretical bases of project management of business which have social character. The logic of a statement of material is under construction as follows. In water part of article authors do the assumption that at the heart of an object of research three basic elements are put: project management, social management and management of social projects. Proceeding from this assumption in work further reasonings are under construction. The main part of article contains three subsections. In the fi rst subsection of article defi nition of the concept «project management» is formulated and methodological approaches to project management (PRINCE2, PERT, the Model Agile, Lean Management, BRM) are generalized. In the second subsection the author's understanding of entity of social management is presented and the main techniques of social management are considered, and also the characteristic of methodology of management of social projects is given. In the third subsection the author's concept of entity of management of social projects of business is formulated. In fi nal part of article authors draw a conclusion about the importance of management of social projects of business. This article, fi rst of all, has theoretical and methodological value for formation of eff ective methods and instruments of management of social projects of business, and also for development of the theory and practice of corporate social responsibility.